A Moral Theory of Public Service Motivation - Wang, Tse-Min; van Witteloostuijn, Arjen; Heine, Florian (Frontiers in Psychology, 2020)
Morality constructs the relationship between the self and others, providing a sense of appropriateness that facilitates and coordinates social behaviors. We start from Moral Foundation Theory (MFT), and argue that multiple moral domains can shape the meaning of public service and engender Public Service Motivation (PSM). From the lens of cognitive science, we develop a causal map for PSM by understanding the social cognition process underlying PSM, focusing on five innate moralities as the potential antecedents of PSM: Care, Fairness, Authority, Loyalty, and Sanctity. Extending moral domains beyond compassion and justice can provide a disaggregated view of PSM, which may help to identify institutional and cultural variation in the meaning of PSM. We discuss the theoretical implications of synthesizing MFT and PSM literatures, and provide directions for future research that could improve our understanding of PSM.